2018
DOI: 10.1063/1.5032161
|View full text |Cite
|
Sign up to set email alerts
|

MHD Kelvin-Helmholtz instability in the anisotropic solar wind plasma

Abstract: We investigated a shear instability of the Kelvin-Helmholtz (KH) type in a plasma with temperature anisotropy under the MHD approximation. To solve the problem, a system of 16-moment MHD transport equations is used in a collisionless Bi-Maxwellian plasma, including the various components of the heat fluxes along the magnetic field. We consider supersonic flows of two semiinfinite anisotropic and homogeneous plasma layers with different physical parameters and velocities. For the general case, i.e. when the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…It follows that even the sub-Alfvénic velocity shear along the fast/slow boundary in the solar corona can lead to KH instability growth, provided that, as expected, the streamer belt region does not have a nicely ordered magnetic field and instead possesses locally a very complicated structure with a nontangential magnetic field configuration. Although theoretically predicted to play an important role in the plasma dynamics between high-and low-speed coronal streams flowing alongside each other (Ismayilli et al 2018), the KH instability has not yet been detected at the edges of coronal holes adjacent to equatorial streamers, where shear due to the outflow of fluids with different velocities can initiate KH vortices. This lack of evidence motivates the present work, which indeed aims at providing, for the first time, possible observational evidence for manifestations of the KH instability in the solar corona in the interaction region between fast and slow solar wind.…”
Section: Introductionmentioning
confidence: 99%
“…It follows that even the sub-Alfvénic velocity shear along the fast/slow boundary in the solar corona can lead to KH instability growth, provided that, as expected, the streamer belt region does not have a nicely ordered magnetic field and instead possesses locally a very complicated structure with a nontangential magnetic field configuration. Although theoretically predicted to play an important role in the plasma dynamics between high-and low-speed coronal streams flowing alongside each other (Ismayilli et al 2018), the KH instability has not yet been detected at the edges of coronal holes adjacent to equatorial streamers, where shear due to the outflow of fluids with different velocities can initiate KH vortices. This lack of evidence motivates the present work, which indeed aims at providing, for the first time, possible observational evidence for manifestations of the KH instability in the solar corona in the interaction region between fast and slow solar wind.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the 16moment formalism has already proven to be successful in analyzing waves and instabilities in weakly collisional media. [32][33][34][35][36] In this paper, we present the stability analysis of the low frequency incompressible perturbations to the anisotropic MHD shear flows with heat fluxes. Effects of the velocity shear and heat fluxes on the dynamics of linear perturbations are characterized by lower frequency compared to the compressibility effects.…”
Section: Aq3mentioning
confidence: 99%
“…For instance, an unstable configuration is found when the velocity jump ∆u is larger than the component of the Alfvén velocity parallel to the bulk flow (Chandrasekhar 1961). Shear flows have been observed, for instance, at the interaction region between fast and slow solar wind (Bruno & Carbone 2013) and both teories and simulations have shown that such sites are good candidates for the KH instability to grow (Korzhov et al 1985;Ismayilli et al 2018). In addition, in such regions, the wave-particle interaction with the non-uniform velocity field can produce smallscale fluctuations leading to the dissipation of the waves (Pezzi et al 2017;Valentini et al 2012Valentini et al , 2017.…”
Section: Introductionmentioning
confidence: 99%